Development of a Web-Based Laundry Service Information System at Syafira Laundry - Shadam Alfareza (Journal of Artificial Intelligence and Engineering Applications (JAIEA), 2025)
In the digital era, the need for fast and easy services encourages business actors to adopt information technology. Syafira Laundry still uses manual recording that is less efficient. This research aims to develop a web-based laundry service information system to improve operational efficiency and service quality. The methods used are the Waterfall model with the stages of needs analysis, system design using UML, implementation with PHP, MySQL, and CodeIgniter and Bootstrap frameworks, and testing using the Blackbox method. The results of the study show that the system built is able to manage transactions, financial reports, and service status in a computerized manner and provide faster and more accurate access to information.